2021
DOI: 10.1186/s42506-020-00064-9
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in out-of-pocket health expenditure among women of reproductive age: after-effects of national health insurance scheme initiation in Ghana

Abstract: Background Improvement in maternal healthcare is a public health priority. Unfortunately, in spite of the efforts made over time regarding universal coverage, there remain issues with accessibility and use of healthcare services up to now. In this study, we examined inequalities in out-of-pocket health expenditure among women of reproductive age in Ghana. We analyzed secondary data collected in Ghana Demographic and Health Survey (GDHS) - 2014. A total of 9,002 women of reproductive age were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The overall findings showed positive results where the beneficiaries had over 50 percent access to key healthcare services at health facilities at the local level in Ghana. This finding concurs with some recent studies on pregnant women' increased access to maternal healthcare services under NHIS in Ghana (Ameyaw et al, 2021;Ekholuenetale and Barrow, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The overall findings showed positive results where the beneficiaries had over 50 percent access to key healthcare services at health facilities at the local level in Ghana. This finding concurs with some recent studies on pregnant women' increased access to maternal healthcare services under NHIS in Ghana (Ameyaw et al, 2021;Ekholuenetale and Barrow, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…There are reasons for such a rate of population coverage of the NHIS, one of which is the access to quality healthcare services. The literature points out that the better the quality of healthcare services, the more the enrolment into NHIS as improving quality healthcare services will enhance the full benefits of the NHIS (Kipo-Sunyehzi, 2020; Ekholuenetale and Barrow, 2021).…”
Section: Literature Review Implementation Of the Nhis And Implementers And Beneficiaries' Perspectives On Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that among vulnerable populations such as migrants in the informal sector, the incidence of OOP payment for healthcare is very high (89.0%) relative to findings from other studies. Akazili et al, (2017) and Ekholuenetale and Barrow (2021) found that rich individuals or households were more likely to incur OOP payments. For example, in their study in Ghana, Akazili et al (2017) found that 10.9% of the population incur OOP payments, and concluded that richer households incurred more OOP relative to poorer ones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their study in Ghana, Akazili et al (2017) found that 10.9% of the population incur OOP payments, and concluded that richer households incurred more OOP relative to poorer ones. Ekholuenetale and Barrow (2021) found that 17% of women from wealthy home paid OOP for health care.…”
Section: Discussionmentioning
confidence: 99%